Sodality Mencari Jalannya Sendiri: Setengah Abad Warisan Pemikiran Sediono M.P. Tjondronegoro - Satyawan Sunito (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
The present review on articles published in this special edition dedicated to Prof. S.M.P. Tjondronegoro focuses on four subject matters. First, on the overall tendency of the articles to focus on the concept sodality and to overlook other intellectual concerns of Tjondronegoro. The second subject deals with the question of why the overwhelming focus of the articles revolves around this concept and this has to do with the understanding of the sodality itself. This concept has been perceived in its most explicit meaning, namely as the smallest territory-based social unit above the household. This understanding ignores the social class aspect of sodality, and the contradiction between the “Desa” which represents the upper class and sodalities which represent the under class at the countryside. This notion of social class was narrated cautiously but by no means unclear by Tjondronegoro. The third subject is on the existence of sodality fifty years after it was firstly launced by Tjondronegoro when the domination of the “Desa” is almost complete, and the status of sodality as analytical concept is questioned. The last subject is on sodality within the broader Indonesian society: how to place sodality in some societies organized dominantly by kinship-based social organizations, predominantly outside Java? One crucial, underlying question run throughout these articles is wether sodality is an intrinsic character of small social units in the Indonesian countryside; or is it something that has to be looked for, developed, and subject to erosion and disintegration?